2021
DOI: 10.1103/physrevlett.127.116601
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Valley Polarization of Itinerant Electrons

Abstract: Memory or transistor devices based on electron's spin rather than its charge degree of freedom offer certain distinct advantages and comprise a cornerstone of spintronics [1]. Recent years have witnessed the emergence of a new field, valleytronics, which seeks to exploit electron's valley index rather than its spin. An important component in this quest would be the ability to control the valley index in a convenient fashion. Here we show that the valley polarization can be switched from zero to one by a small … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The effect of electron-electron and electron-phonon interaction on valley polarization was examined recently. In an itinerant electron system, Hossain et al [140] demonstrated theoretically that the electron-electron interaction prefers singlevalley occupancy of electrons below a critical density. Consequently, one can switch the valley polarization from 0 to 1 by a small reduction in density and thus design a valleytronic transistor device.…”
Section: Recent Progress Of Valleytronics Beyond Graphenementioning
confidence: 99%
“…The effect of electron-electron and electron-phonon interaction on valley polarization was examined recently. In an itinerant electron system, Hossain et al [140] demonstrated theoretically that the electron-electron interaction prefers singlevalley occupancy of electrons below a critical density. Consequently, one can switch the valley polarization from 0 to 1 by a small reduction in density and thus design a valleytronic transistor device.…”
Section: Recent Progress Of Valleytronics Beyond Graphenementioning
confidence: 99%
“…the prominent K and −K valleys in 2D hexagonal materials) [4,5]. Up to now, several external strategies have been experimentally confirmed to be effective for eliminating the valley degeneracies, such as optical pumping [6,7], magnetic doping [8,9], magnetic proximity [10], external magnetic field [11][12][13], and electric field [14][15][16]. However, these approaches have various insurmountable drawbacks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Here there is no uniaxial strain applied so that the two inplane valleys (X and Y), with their major axes along [100] and [010], are equally occupied at high densities; R [100] and R [010] are essentially equal and the 2DES is isotropic. As n is lowered below 6.3 (r s 20), all the electrons suddenly transfer to the Y valley, leading to R polarization, which is akin to Bloch spin ferromagnetism transition, has been discussed in detail elsewhere [43]; see also [58]. At lower densities, when n 3.2 (r s 28), the 2DES turns insulating as signaled by the temperature dependence of R [100] and R [010] at low temperatures; see Figs.…”
mentioning
confidence: 96%
“…Strong electron-electron interaction in clean twodimensional electron systems (2DESs) leads to a plethora of many-body phases such as fractional quantum Hall liquid [1], Wigner solid (WS) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], and correlated magnetism [16,[22][23][24][25][26][27][28][29]. Anisotropy introduces a new flavor to the interaction phenomena and triggers yet another set of unexpected correlated phases [30][31][32][33][34][35][36][37][38][39][40][41][42][43], such as nematic quantum Hall states [32, 34-36, 40, 42]. A tantalizing example of Fermi sea anisotropy induced many-body states is a theoretically proposed anisotropic WS at zero magnetic field [30].…”
mentioning
confidence: 99%